Encounters with difference: Mental health nurses and Indigenous Australian users of mental health services. (4th April 2019) - Molloy, Luke; Walker, Kim; Lakeman, Richard; Lees, David
Abstract: This article presents findings from the multi‐sited ethnography of mental health nursing practice as it relates to the care of Indigenous users of public mental health services in Australia. It provides an analysis of mental health nurses beliefs and ideas about Aboriginal and Torres Strait Islander people encountered over the course of this research. The Indigenous service user was positioned as Other to the non‐Indigenous mental health nurse, and to non‐Indigenous service users. Cultural difference and the legacy of colonization, including its impact on the health of Aboriginal and Torres Strait Islander peoples, contributed to these beliefs of alterity. Despite emphasizing the differences with Aboriginal and Torres Strait Islander people in mental health services, nurses did not clearly relate this to Indigenous ways of understanding ill health. While cultural differences were recognized, what they meant for the nurses or their nursing practice was interpreted in different ways. In these circumstances, approaches towards care for Aboriginal and Torres Strait Islander people varied between nurses.